Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Section 6.1 - The Greatest Common Factor - Vocabulary and Readiness Check: 6

Answer

FALSE

Work Step by Step

$3x^3+6x+x^2+2 = 3x(x^2+2) + 1(x^2+2) = (3x + 1)(x+3)$ The factor form is $(3x + 1)(x+3)$ and not $ 3x(x^2+2) $ because : $ 3x(x^2+2) = 3x^2 + 6x \ne 3x^3+6x+x^2+2$ for example $x=1$ $ 3x(x^2+2) = 9 \ne 12 = 3x^3+6x+x^2+2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.